Willingness to pay for National Health Insurance Fund among public servants in Juba City, South Sudan: a contingent evaluation - Robert Basaza; Paul Kon Alier; Peter Kirabira; David Ogubi; Richard Lino Loro Lako (BMC, 2017)
Abstract Background This study assessed willingness to pay for National Health Insurance Fund (NHIF) among public servants in Juba City. NHIF is the proposed health insurance scheme for South Sudan and aims at achieving universal health coverage for the entire nation's population. One compounding issue is that over the years, governments' spending on healthcare has been decreasing from 8.4% of national budget in 2007 to only 2.2% in 2012. Methods A cross-sectional study design using contingent evaluation was employed; data on willingness to pay was collected from 381 randomly selected respondents and 13 purposively selected key informants working for the national, state and Juba County in September 2015. Qualitative data were analysed using conceptual content analysis. T-tests and linear regressions were performed to determine association between WTP for NHIF and independent variables. Results Up to 381 public servants were interviewed, of which 68% indicated willingness to pay varying percentages of total monthly individual income for NHIF. Over two-thirds (67.8%) of those willing to pay could pay up to 5% of their total monthly income, 22.9% could pay up to 10% and the rest could pay 25%. Over 80% were willing to pay up to 50 SSP (1 USD = 10 SSP) premiums for medical consultation, laboratory services and drugs. The main factors influencing the respondents' decisions were awareness, alternative sources of income, household size, insurance cover and religion. Conclusions Willingness to pay is mainly influenced by awareness, alternative sources of individual income, household size, insurance cover and religion. Most of the public servants were aware of and willing to pay for NHIF and prefer a premium of up to 5% of total monthly income. There is need to create awareness and reach out to those who do not know about the scheme in addition to a detailed analysis of other stakeholders. Consideration could be made by the Government of South Sudan to start the scheme at the earliest opportunity since the majority of the respondents were willing to contribute towards it.